Congenital renal hypoplasia and contralateral kidney failure in a giant otter (Pteronura brasiliensis) ex situ in Southeastern Brazil - Ribeiro, Vanessa Lanes; Kokubun, Hanna Sibuya; Riva, Henrique Guimarães; Nemer, Viviane Cristhiane; Bianchi, Matheus Viezzer; Costa, André Luiz Mota da; Teixeira, Rodrigo Hidalgo Friciello (Brazilian Journal of Veterinary Pathology, 2023)
Renal hypoplasia is incomplete development of the kidneys, in which fewer than normal numbers of nephrons are present at birth. This report is the first of these conditions in mustelids. A female adult giant otter (Pteronura brasiliensis), ex situ, presented clinically an unusual behavior with prostration, anorexia, hiding in the shelter, ataxia, paraparesis, and death in a clinical course of one day. At the postmortem exam, the left kidney was markedly enlarged and pale and the right kidney was severely reduced and had mild to moderate capsular thickening. Histologically, the left kidney had mineralization, proliferation of fibrous connective tissue and a mild neutrophilic infiltrate. The right kidney presented a reduced number of glomeruli, tubular atrophy and an increase in fibrous connective tissue, which were findings compatible with congenital kidney hypoplasia. Due the clinical condition of the animal, gross and microscopic findings, the cause of death was established as kidney failure induced by renal hypoplasia.